EXPERIENCE OF PERCUTANEOUS CORONARY INTERVENTION OF CHRONIC TOTAL OCCLUSION IN NATIVE CORONARY ARTERIES - Islam, Zafar Ul; Yaqoob, Naveed; Adnan, Raja (Pakistan Armed Forces Medical Journal, 2011)
Objectives: To evaluate the procedural outcome and periprocedural complications of PCI in CTO. Study Design: Observational study Place and Duration of Study: during 2008 at AFIC/NIHD. Patients and Methods: This study was carried out on 311 patients with 319 Chronic total occlusion (CTOs) who underwent precutaneous coronary intervention (PCI) in catheterization laboratory at AFIC/NIHD. Patients with total occlusions less than three months duration were excluded. After informed consent data was gathered on standard proforma and was analyzed using SPSS 13.0 Results: Out of 311 patients, 264 were males and 47 were females, ranging in age from 30 years to 80 years. Technical success was obtained in 78% of patients and procedural success in 76%. Most common location was LAD 48.2% followed by RCA 32.5%, LCx 18.6%, and LMS 0.6%. Technical success in LAD was 48.3%, RCA was 30.6%, LCx was 20.2% and LMS was 0.8% of the total successful PCIs. Among failed procedures inability to cross the lesion with a guidewire and inability to adequately dilate the lesion with balloon were the reasons of failure in 82.6% and 17.4% patients respectively.No patient died, three patients suffered MI, one patient underwent urgent coronary artery bypass surgery (CABG) and two patients underwent urgent repeat PCI. Conclusion: PCI to CTO is a safe procedure in carefully selected patients and should be offered as a revascularization modality.